Should miliary tuberculosis be considered as a possible cause of infertility in the new era: a case report and literature review - Cvetkovic, Aleksandra; Blanka Protic, Ana; Jovanovic, Jelena; Adzic Vukicevic, Tatjana (Frontiers in Medicine, 2025)
IntroductionMiliary tuberculosis (MTB) is a potentially lethal form of tuberculosis that can occur in pregnant women, especially those who have conceived by in vitro fertilization (IVF).Case descriptionA 28-year-old, female patient, after IVF’s fourth attempt, at the end of the first trimester, developed a dry cough, high fever, abdominal pain, and vaginal bleeding, which led to the pregnancy termination without resolution of systemic symptoms despite various antibiotics. Because of the appearance of headaches, brain nuclear magnetic resonance (NMR) was done, and diffuse nodular brain lesions were found, which were initially interpreted as metastatic cancer disease. Afterward, the miliary changes were discovered in various organ systems, and the presence of Mycobacterium tuberculosis was confirmed. The antituberculosis treatment was initiated with the standard antituberculosis regimen with excellent clinical response and resolution of miliary changes.ConclusionMiliary tuberculosis is more common in cases of pregnancies related to IVF. It should be taken into consideration as a possible risk for infertility in the presence of nonspecific symptoms. Screening methods for latent tuberculosis in IVF patients are needed even in a low-burden TB country.